Exosomes in human atherosclerosis: An ultrastructural analysis study. (3rd March 2016) - Perrotta, Ida; Aquila, Saveria
ABSTRACT: Cell-to-cell communication, or signaling, is absolutely essential in orchestrating the activities of cells in multicellular organisms, to grow, develop, detect environmental changes and compensate for them in an internal, coordinated fashion. In the last few years, a considerable amount of new data have demonstrated the occurrence of a sophisticated intercellular signaling pathway based on the release of specialized vesicular structures, called exosomes, whose secretion appears to be regulated by various natural and experimental stimuli, physiological states, and disease processes. In the cardiovascular system, the study of exosomes is still in its infancy. Here, we aim to provide the first ultrastructural evidence for the presence of exosomes in human atherosclerotic plaque. We demonstrate by means of transmission electron microscopy that both lesional smooth muscle cells and endothelial cells are able to generate these membraneous microvesicles within specific compartments of the cell, called multivesicular bodies. Notably, in our series no signs of apoptosis have been detected in vascular cells secreting exosomes and no evidence of calcification has been observed associated with these structures in the extracellular space. Our results suggest the possible existence of a new mechanism of intercellular communication in the plaque milieu.